A Literature Review On Linguistic And Psychological Barriers In Speaking English In Islamic Educational Contexts - Elvia Mutiara Ikhsani; Siti Maulani Delfina; Rizky Miftahul Jannah; Wirdatul Husna; Mela Novianti; Santy Agustin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Speaking ability is considered one of the most significant competencies in English language learning because it allows learners to convey ideas, perspectives, emotions, and information through oral communication. Within the context of English as a Foreign Language (EFL), speaking competence functions as an important indicator of language proficiency since successful communication is closely associated with learners’ ability to interact effectively, fluently, and appropriately in diverse communicative situations. Nevertheless, despite the important role of speaking ability in language learning, many EFL learners continue to encounter considerable challenges in developing effective oral communication skills, particularly in Islamic educational contexts where classroom culture, learning environments, and psychological conditions may influence learners’ participation in speaking activities. This article aims to critically examine and synthesize previous studies related to linguistic and psychological barriers that affect learners’ speaking ability within Islamic educational contexts. The study applies a qualitative literature review approach through the analysis of academic books, scholarly journal articles, and previous empirical studies concerning speaking difficulties experienced by EFL learners. The findings demonstrate that linguistic barriers, including limited vocabulary mastery, grammatical inaccuracies, and pronunciation difficulties, significantly influence learners’ ability to communicate effectively in English. In addition, psychological barriers such as speaking anxiety, fear of making mistakes, lack of self-confidence, and fear of negative evaluation also contribute substantially to learners’ speaking difficulties. The review further indicates that psychological barriers tend to exert a more dominant influence on speaking performance because these factors directly affect learners’ confidence and willingness to engage in oral communication activities. Furthermore, classroom interaction patterns and learning environments within Islamic educational institutions may also influence learners’ speaking participation and communication confidence. Therefore, English language instruction in Islamic educational contexts should not only emphasize the development of linguistic competence but also foster supportive and psychologically secure learning environments that encourage learners to participate confidently and actively in speaking activities